2022
DOI: 10.1002/vms3.942
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram and virulence profiling reveals multidrug resistantStaphylococcus aureusas the predominant aetiology of subclinical mastitis in riverine buffaloes

Abstract: Background Staphylococcus spp. are the major causal agents of mastitis in dairy animals worldwide leading to profound economic losses and public health threats. Recently, Staphylococcus aureus has emerged as a multidrug resistant and zoonotic pathogen. This study aimed to characterize S. aureus in subclinical mastitis (SCM) milk samples of riverine buffaloes in Bangladesh through antibiogram and virulence gene(s) profiling, and 16S rRNA gene sequencing. Method We characterized S. aureus in SCM milk samples (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 64 publications
(136 reference statements)
1
20
0
Order By: Relevance
“…Our study performed in a buffalo farm determined a statistically significant higher level of IMI (62%) than SCM (11%) cases, with no cases of CM. Several studies have analyzed the prevalence of SCM in buffalo populations around the world, reporting a prevalence of approximately 26.2% and 37.6% in India and Bangladesh, respectively [28,29]. The meta-analysis work conducted by Krishnamoorthy et al [30] on numerous studies published worldwide during the period 1967-2019 has identified values of 46% and 32% for SCM cases in buffaloes worldwide and in India, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our study performed in a buffalo farm determined a statistically significant higher level of IMI (62%) than SCM (11%) cases, with no cases of CM. Several studies have analyzed the prevalence of SCM in buffalo populations around the world, reporting a prevalence of approximately 26.2% and 37.6% in India and Bangladesh, respectively [28,29]. The meta-analysis work conducted by Krishnamoorthy et al [30] on numerous studies published worldwide during the period 1967-2019 has identified values of 46% and 32% for SCM cases in buffaloes worldwide and in India, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The Pearson’s chi-square test was performed to compare the prevalence of P. aeruginosa in three different sample categories (e.g., clinical, environment and poultry). A prevalence percentage was calculated by dividing the number of positive samples for the given category by the total samples tested within that category [29, 30]. The prevalence formula was applied for determining prevalence percentage of Pseudomonas and P. aeruginosa .…”
Section: Methodsmentioning
confidence: 99%
“…There are several methods for determining the antimicrobial susceptibility of causative pathogens of bubaline mastitis, such as the disk diffusion method, microdilution assay, and PCR (Clinical Laboratory Standards Institute [CLSI], 2019; Hoque et al, 2022). Disk diffusion method is commonly used to determine the antimicrobial susceptibility causative pathogens of bubaline mastitis in Asia countries because it is simple, reliable, and can detect the isolated resistant colonies (Mayrhofer et al, 2008;Milici et al, 2007).…”
Section: Antimicrobial Susceptibility Of Causative Agents Of Bubaline...mentioning
confidence: 99%
“…Disk diffusion method is commonly used to determine the antimicrobial susceptibility causative pathogens of bubaline mastitis in Asia countries because it is simple, reliable, and can detect the isolated resistant colonies (Mayrhofer et al, 2008;Milici et al, 2007). PCR detected the virulence genes in isolated bacteria (Hoque et al, 2022).…”
Section: Antimicrobial Susceptibility Of Causative Agents Of Bubaline...mentioning
confidence: 99%